1989
DOI: 10.1111/j.1752-0606.1989.tb00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Marital Satisfaction, and Marital and Personality Measures of Sex Roles*

Abstract: The present study examined the relationship between depression, marital satisfaction, and marital and personality measures of sex roles. Subjects included 50 couples in which the woman was clinically depressed (and of which 26 were maritally distressed), and 24 nondepressed, nondistressed control couples. Results indicated that compared to nondepressed couples, husbands and wives in relationships in which the wife was depressed showed greater inequality in decision making and dissatisfaction with the distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 42 publications
3
21
1
Order By: Relevance
“…However, these results are also consistent with a stress and coping formulation in which withdrawal and passive aggression are coping strategies used to manage the stressful demands that may be perceived to exceed depressed female partners' personal resources (Huang, 1991). In contrast to some previous research, our results suggest a unique link between depression and dissatisfaction with decision-making and childcare arrangements (Whisman and Jacobson, 1989).…”
contrasting
confidence: 56%
“…However, these results are also consistent with a stress and coping formulation in which withdrawal and passive aggression are coping strategies used to manage the stressful demands that may be perceived to exceed depressed female partners' personal resources (Huang, 1991). In contrast to some previous research, our results suggest a unique link between depression and dissatisfaction with decision-making and childcare arrangements (Whisman and Jacobson, 1989).…”
contrasting
confidence: 56%
“…In a similar fashion, it is proposed that maximum marital satisfaction is achieved when couples live in a marital environment which is guided by a power system that is acceptable to the spouses. This suggests that there are spouses who feel happy in democratic relationships and there are spouses who feel happy in husband-or wifedominated relationships; the ideal power varies from one couple to another (Whisman and Jacobson 1989). This is the position reported by Coleman and Straus (1986) when they argue that although egalitarian couples have lower rates of conflict they also state that consensus about the legitimacy of (female or male) dominance in the relationship reduces conflict and violence in families.…”
Section: Type Of Power and Marital Happinessmentioning
confidence: 81%
“…Researchers have consistently found that relationship equality (e.g., shared power, decision making, and household and child-rearing tasks) is associated with higher levels of relationship satisfaction, commitment, and emotional well-being for married women (Gottman, 1999;Gray-Little & Burks, 1983;Lange, 1989;Moller, Hwang, & Wickberg, 2008;Ross, Mirowsky, & Huber, 1983;Steil, 1997;Whisman & Jacobson, 1989, 1990Zimmerman, 2000). For example, Lange found that the more equal heterosexual women perceived their relationship to be the more committed they were to their relationship.…”
Section: Relationship Equalitymentioning
confidence: 96%